Tekst in podtekst v Bartolovi kritiki Vidmarjevih Literarnih kritik - Virk, Tomo (Slavistična revija, 2025)
In 1952, Vladimir Bartol published a comprehensive review of Josip Vidmar's Literary Criticism. In it, he also discussed some general questions of literary criticism and historiography in detail. Bartol's diary entries will be used to show that Bartol's outwardly neutral discourse concealed a personally motivated vision of reshaping literary history in such a way that it could adequately evaluate his own literary work.
Keywords: Bartol, Vladimir; literarna kritika; literarna zgodovina; literary criticism; literary history; Slovene literature; slovenska književnost; Vidmar, Josip